Consumer culture, precarious incomes and mass indebtedness: Borrowing from uncertain futures, consuming in precarious times. (February 2022) - Lloyd, Anthony; Horsley, Mark
In recent years, labour markets have been characterised by stagnant wages, reduced incomes and growing insecurity supplemented by the ongoing proliferation of outstanding payment obligations at almost all levels of economy and society. We draw upon current debates in social and economic theory to explore the disconnect between the deterioration of late capitalism's distributive measures and the relative vitality of consumer cultures, suggesting that the latter relies substantially on immaterial, credit-based payment means to bridge the gap between the fundamental fantasy of 'more and better' and the decline of material productivity denoted by base rate of profit. We then use this disconnect as a breach-point for an in-depth interdisciplinary discussion of the substantive and ideological function of credit.